Extrastriatal Dopaminergic Circuits of the Basal Ganglia - Rommelfanger, Karen S.; Wichmann, Thomas (Frontiers in Neuroanatomy, 2010)
The basal ganglia are comprised of the striatum, the external and internal segment of the globus pallidus (GPe and GPi, respectively), the subthalamic nucleus (STN), and the substantia nigra pars compacta and reticulata (SNc and SNr, respectively). Dopamine has long been identified as an important modulator of basal ganglia function in the striatum, and disturbances of striatal dopaminergic transmission have been implicated in diseases such as Parkinson's disease (PD), addiction and attention deficit hyperactivity disorder. However, recent evidence suggests that dopamine may also modulate basal ganglia function at sites outside of the striatum, and that changes in dopaminergic transmission at these sites may contribute to the symptoms of PD and other neuropsychiatric disorders. This review summarizes the current knowledge of the anatomy, functional effects and behavioral consequences of the dopaminergic innervation to the GPe, GPi, STN, and SNr. Further insights into the dopaminergic modulation of basal ganglia function at extrastriatal sites may provide us with opportunities to develop new and more specific strategies for treating disorders of basal ganglia dysfunction.